2004
DOI: 10.1038/sj.bmt.1704611
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion idarubicin and oral busulfan as conditioning for patients with acute myeloid leukemia aged over 60 years undergoing autologous stem cell transplantation

Abstract: Summary:There is growing interest in autologous stem cell transplantation (ASCT) for elderly patients with acute myeloid leukemia (AML). While mortality and toxicity from ASCT have been reduced, relapse rate is still high. In a prospective study, we investigated the feasibility of a new conditioning regimen consisting of high-dose idarubicin plus busulfan in AML patients aged over 60 years undergoing ASCT. A total of 14 patients (median age: 64 years) received 2 days continuous infusion of idarubicin at 20 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Most patients were conditioned to ASCT with c.i. idarubicin and oral busulphan with a schedule adapted by age as previously described [24,25] and there was no difference between young adult and elderly patients as transplant related mortality and haematopoietic recovery is concerned (data not shown).…”
Section: Patient Characteristicsmentioning
confidence: 81%
“…Most patients were conditioned to ASCT with c.i. idarubicin and oral busulphan with a schedule adapted by age as previously described [24,25] and there was no difference between young adult and elderly patients as transplant related mortality and haematopoietic recovery is concerned (data not shown).…”
Section: Patient Characteristicsmentioning
confidence: 81%
“…Following consolidation, G-CSF was given at a dose of 10 mg kg 71 from day 15 with the aim of shortening neutropenia and mobilizing CD34þ cells. All patients in whom collection of CD34þ cells was successful (42 6 10 6 kg 71 ) were programmed to be given ASCT with a conditioning regimen consisting of high dose intravenous continuous infusion idarubicin plus busulphan, as previously described [28]. More in detail, high-dose idarubicin administered at 20 mg m 72 per day as CI for 2 days (day -11 to day -10) followed by oral busulphan given at 4 mg kg 71 per day from day -4 to day -2.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a substantial reduction of morbidity and mortality has been definitively confirmed following the adoption of PBSC [13]. In a small series of 14 patients, we previously described results achieved with ASCT after conditioning with an original combination regimen including Ida and Bu [22]. Such a regimen was specifically designed for AML, with the aim of reducing relapse rate which, differently from toxicity, remains substantially unmodified in patients autografted with PBSC.…”
Section: Discussionmentioning
confidence: 99%
“…In the autologous setting, alternative chemotherapy combinations have been proposed with the aim of inducing a superior anti-leukaemic activity [20,21]; in particular, in a preliminary study on older AML patients we reported the feasibility and the potential efficacy of a new conditioning regimen, consisting of a combination of 2 days continuous infusion (c.i.) idarubicin (IDA) at a dose of 20 mg/m 2 followed by 3 days standard oral dose busulphan (Bu), termed BuI [22]. Here we report therapeutic results from a larger series of 40 AML patients older than 60 years with a longer follow up who were autografted in CR1 after conditioning with BuI regimen.…”
Section: Introductionmentioning
confidence: 97%